Stream temperature response to variable glacier coverage in coastal watersheds of Southeast Alaska. Issue 4 (12th March 2013) - Fellman, Jason B.; Nagorski, Sonia; Pyare, Sanjay; Vermilyea, Andrew W.; Scott, Durelle; Hood, Eran
Abstract We measured stream temperature continuously during the 2011 summer run‐off season (May through October) in nine watersheds of Southeast Alaska that provide spawning habitat for Pacific salmon. The nine watersheds have glacier coverage ranging from 0% to 63%. Our goal was to determine how air temperature and watershed land cover, particularly glacier coverage, influence stream temperature across the seasonal glacial meltwater hydrograph. Multiple linear regression models identified mean watershed elevation (related to glacier extent) and watershed lake coverage (%) as the strongest landscape controls on mean monthly stream temperature, with the weakest (May) and strongest (July) models explaining 86% and 97% of the temperature variability, respectively. Mean weekly stream temperature was significantly correlated with mean weekly air temperature in seven streams; however, the relationships were weak to non‐significant in the streams influenced by glacial run‐off. Streams with >30% glacier coverage showed decreasing stream temperatures with rising summer air temperatures, whereas those with <30% glacier coverage exhibited summertime warming. Glaciers also had a cooling effect on monthly mean stream temperature during the summer (July through September) equivalent to a decrease of 1.1 °C for each 10% increase in glacier coverage. The maximum weekly average temperature (an index of thermal suitability for salmon) in the six glacial streams was substantially below the lower threshold for optimum salmon growth. This finding suggests that although glaciers are important for moderating summer stream temperatures, future reductions in glacier run‐off may actually improve the thermal suitability of some glacially dominated streams in Southeast Alaska for salmon. Copyright © 2013 John Wiley & Sons, Ltd.